Las costumbres de mi localidad, la marinera - Elias Asto, Candy Yany (2018)
The present professional sufficiency research on the learning sesión desing, with the ability Live together and participate democratically in the search for the common good and performance: They carry out daily activities with their classmates and take interest in knowing their customs, as well as their hometown. Ask questions about what caught their attention, which will result in the children of the “Hermanos Blanco” Kinder Garden in Trujillo city showing interest in learning about the customs in their locality, describing and expressing their ideas spontaneously. On the other hand, democratic coexistence and participation in the search for the common welfare will allow children to strengthen their interpersonal relationships and interaction with family, society and culture.